The Use of The TPR Storytelling Method in Teaching Speaking Skills of Physical Education Students - Muliaty Ibrahim; Hasnani Hasnani; Muhammad Yahrif; Yulini Rinantanti (DEIKTIS: Jurnal Pendidikan Bahasa dan Sastra, 2024)
This research investigates the effectiveness of the Total Physical Response (TPR) Storytelling method in improving the speaking skills of physical education students. The study employs a quasi-experimental design involving two groups: an experimental group that received instruction using the TPR Storytelling method and a control group that followed a traditional teaching approach. Data were collected through pre-tests and post-tests to measure the students’ speaking abilities, along with observations and interviews to gain qualitative insights into the learning process. The findings reveal that students in the experimental group demonstrated a significant improvement in their speaking skills compared to those in the control group. The TPR Storytelling method was found to be particularly effective in engaging students and promoting active participation, which led to enhanced vocabulary usage, better sentence construction, and increased confidence in speaking. The qualitative data supported these results, showing that students were more motivated and showed a higher level of enthusiasm towards learning English through storytelling. This research highlights the potential of the TPR Storytelling method as a valuable tool in language teaching, especially for students in non-language disciplines such as physical education. The study recommends that educators consider incorporating this method into their teaching practices to foster more dynamic and interactive language learning environments